1997
DOI: 10.1364/josab.14.002469
|View full text |Cite
|
Sign up to set email alerts
|

Narrow-band tunable extreme-ultraviolet laser source for lifetime measurements and precision spectroscopy

Abstract: A narrow-band, extreme-ultraviolet laser source is developed that has continuous tunability in the range 96-97.5 nm and a bandwidth below 250 MHz. The versatility of the radiation source is demonstrated in two applications. Accurate values for lifetimes of highly excited molecular quantum states are determined from line-broadening measurements in three electronic states of CO:The application of the source in metrology in the extreme-ultraviolet domain is demonstrated by the highly accurate, absolute calibratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
60
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 26 publications
1
60
0
Order By: Relevance
“…Rotational and parity (e/f) resolved lifetimes of L 1 Π, W 1 Π and K 1 Σ + excited states have been experimentally determined using a narrow band extreme-UV laser source 46 . For the W 1 Π state, a radiative lifetime of 4 nanosecond was derived 47 through ab initio calculations.…”
Section: Isotopic Fractionation: Band Specific Observationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rotational and parity (e/f) resolved lifetimes of L 1 Π, W 1 Π and K 1 Σ + excited states have been experimentally determined using a narrow band extreme-UV laser source 46 . For the W 1 Π state, a radiative lifetime of 4 nanosecond was derived 47 through ab initio calculations.…”
Section: Isotopic Fractionation: Band Specific Observationsmentioning
confidence: 99%
“…For the W 1 Π state, a radiative lifetime of 4 nanosecond was derived 47 through ab initio calculations. Convoluting the experimentally determined natural lifetime of 130 ps with the radiative lifetime, Ubachs et al 46 concluded that the Π f (f-parity) component of W 1 Π (v=0) state is predissociated by 96.6 % and the 3.3% radiative decay will populate the vibrationally excited states of the electronic ground state. The experimentally determined 1.0 nanosecond lifetime of (4pπ)L 1 Π, ν=0 was suggested to be an effect of purely radiative decay 46 .…”
Section: Isotopic Fractionation: Band Specific Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Relative frequency measurements are performed by comparing the XUV spectrum with the transmission markers of an actively stabilized etalon, for which the visible output of the ring-dye laser at the fundamental wavelength is used. While in absolute measurements the accuracy of the frequency scale is limited by chirp effect in the PDA system, 26 for the present relative measurements, the uncertainty is reduced to a few megahertz as the chirp effect is considered to be equal over the small frequency intervals of the scans. Hence the uncertainty in the derived hyperfine parameters is primarily due to the statistics of the fitting procedures.…”
Section: Methodsmentioning
confidence: 96%
“…26 In short, the output of a continuous-wave ring-dye laser operating near 570 nm is amplified in a three-stage pulsed-dye amplifier ͑PDA͒, then frequency-doubled in a KDP nonlinear crystal and subsequently frequency tripled in a pulsed jet of xenon gas. Coherent radiation, tunable in the wavelength range near 95 nm is produced in a forwardly directed beam at sub-nanojoule pulse energies and at a bandwidth of 250-350 MHz, depending on specific alignment and conditions.…”
Section: Methodsmentioning
confidence: 99%